Варга: [Фотокнижка : Для мл. шк. возраста]; Пересказ [с норвеж.] / А. Увесен ; пересказ: А. Онегова, Ю. Каржавиной - Увесен Алберт (Дет. лит, 1986)
Экземпляры: ДБ (1986) / Инвентарный номер: 12227 / Цена: 1.50 / Сис.шифр: 28.68 / Авт.знак: У 18 / ББК: 28.685(4Нр) я6